Slavery and the rise of the Atlantic system - Solow, Barbara L. (Barbara Lewis). (Cambridge, Mass. W.E.B. DuBois Institute for Afro-American Research, Harvard University, 1991)
For review see: Roderick A. McDonald, in The economic historic review : a journal of economic and social history, vol. 46, no. 2 (May 1993); p. 423-424. - Hiliary Beckles, in Slavery and Abolition : a journal of slave and post-slave studies, vol. 14, nr. 2 (August 1993); p. 128-129. - The essays in this book (e.g. by Pieter Emmer) describes e.g. the transfer of slavery from the Old World, its role in forging the interdependence of the economics bordering the Atlantic, its effect on the empires of Portugal, The Netherlands, France and Great Britain, and its impact on Africa.
Slavery and colonization / Barbara L. Solow -- The Old World background of slavery in the Americas / William D. Phillips, Jr. -- Slavery and lagging capitalism in the Spanish and Portuguese American empires, 1492-1713 / Franklin W. Knight -- The Dutch and the making of the second Atlantic system / P.C. Emmer -- Precolonial western Africa and the Atlantic economy / David Eltis -- A marginal institution on the margin of the Atlantic system : the Portuguese southern Atlantic slave trade in the eighteenth century / Joseph C. Miller -- The apprenticeship of colonization / Luiz Felipe de Alencastro -- Exports and the growth of the British economy from the Glorious Revolution to the Peace of Amiens / P.K. O'Brien and S.L. Engerman -- The slave and colonial trade in France just before the Revolution / Patrick Villiers -- Slavery, trade, and economic growth in eighteenth-century New England / David Richardson -- Economic aspects of the growth of slavery in the seventeenth-century Chesapeake / David W. Galenson -- Credit in the slave trade and plantation economies / Jacob M. Price.
Includes bibliographical references and index.
Keywords: Slave trade -- Africa -- Congresses; Slave trade -- Europe -- Congresses; Slave trade -- America -- Congresses; Esclavitud -- Comercio -- Europa; Esclavitud -- Comercio -- Amâerica; Slaves -- Trades; Aufsatzsammlung; KongreÇ -- Cambridge (Mass.) -- 1988.